Meeting Questions (2010)
Why are there waves in the sea? How to clean the water on our planet? Why was school invented? Why do people work? How were numbers created? Why do colors exist? , How is virtual reality created? These are some of the questions that children have asked at EAFIT Children's University and that we seek to solve in our encounters through play, conversation and experimentation.